2016
DOI: 10.21082/jhort.v23n3.2013.p255-262
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Metode Pembekuan Terhadap Karakteristik Irisan Buah Mangga Beku Selama Penyimpanan

Abstract: ABSTRAK.Dalam upaya mengurangi terjadinya kehilangan hasil buah-buahan terutama selama periode penyimpanan, distribusi, dan pemasaran, perlu aplikasi perlakuan yang efektif. Salah satu cara yang sering dilakukan ialah melalui pembekuan. Penelitian dilaksanakan dari Bulan Juli 2007 hingga Februari 2008. Tujuan penelitian ialah mengevaluasi mutu irisan buah mangga beku selama penyimpanan. Buah mangga terlebih dahulu dicuci, kemudian dikupas, dan diiris menjadi bentuk kubus (2x2x2 cm) dengan berat 250 g untuk set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
3
1
3
Order By: Relevance
“…Vitamin C in podang urang mango extract 28.32 mg/100 g. Titratable acid in podang urang mango extract was 0.12 %. Its lower than those reported by Amiarsi and Mulyawanti [22] who found that vitamin C in mango was 33.62-58.59 mg/100 g and titratable acid was 0.11%. This acidity was caused by organic acid such as acetic acid, ascorbate, citrate, butyrate, and propionate [23].…”
Section: Resultscontrasting
confidence: 60%
“…Vitamin C in podang urang mango extract 28.32 mg/100 g. Titratable acid in podang urang mango extract was 0.12 %. Its lower than those reported by Amiarsi and Mulyawanti [22] who found that vitamin C in mango was 33.62-58.59 mg/100 g and titratable acid was 0.11%. This acidity was caused by organic acid such as acetic acid, ascorbate, citrate, butyrate, and propionate [23].…”
Section: Resultscontrasting
confidence: 60%
“…Namun sebelum di bekukan buah mangga memiliki perlakuan khusus. Irisan buah mangga segar dengan kematangan komersial (80-90%) akan dicelupkan ke dalam nitrogen cair selama 40 detik dan disimpan di dalam freezer [4]. Karena indonesia sebagai negara tropis, pemerintah Indonesia saat ini sedang giat dalam mengembangkan energi surya yang cukup besar.…”
Section: Pendahuluanunclassified
“…Dalam proses pembekuan yang baik biasanya berkisar antara -12 o C sampai dengan -24 o C [6]. Penyimpanan beku pada suhu kabin sekitar -18 o C dan dibawahnya dapat mencegah kerusakan mikrobiologi, dengan syarat tidak terjadi fluktuasi suhu yang terlalu besar [4].…”
Section: Pendahuluanunclassified
“…According to Amiarsi & Mulyawanti (2013), the increase in sugar concentration in fruit that occurs during slow freezing causes the physiological process that remodels organic components into sugar to take longer. The ability to maintain the taste of the freeze-dried strawberries is caused by the drying process running well with an indication of the formation of pores in the fruit.…”
Section: Total Dissolved Solid (Tds)mentioning
confidence: 99%
“…The ability to maintain the taste of the freeze-dried strawberries is caused by the drying process running well with an indication of the formation of pores in the fruit. This also shows that during the freezing process, strawberries do not experience chilling injury which generally occurs because strawberries are a very sensitive horticultural commodity during handling and storage (Amiarsi & Mulyawanti, 2013). Hariyadi (2013) states that the physical structure of freeze-dried food products can be maintained during the freeze-drying process, and the overall drying process takes place at low temperatures, so the freezedried food produced will be able to maintain color, shape, texture, and flavor.…”
Section: Total Dissolved Solid (Tds)mentioning
confidence: 99%